2016
DOI: 10.1152/ajpcell.00229.2015
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of a protein transduction domain-mediated Prdx6 protein ameliorates oxidative stress-induced injury in human and mouse neuronal cells

Abstract: Singh SP, Chhunchha B, Fatma N, Kubo E, Singh SP, Singh DP. Delivery of a protein transduction domain-mediated Prdx6 protein ameliorates oxidative stress-induced injury in human and mouse neuronal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…PRDX6 is a protective protein with GSH peroxidase. Studies showed that PRDX6 could scavenge reactive oxygen species (ROS) to regulate cellular physiology (Singh et al, ). Inhibition of the expression of PRDX6 could increase the ROS level (Zha et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…PRDX6 is a protective protein with GSH peroxidase. Studies showed that PRDX6 could scavenge reactive oxygen species (ROS) to regulate cellular physiology (Singh et al, ). Inhibition of the expression of PRDX6 could increase the ROS level (Zha et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Its use is children is specifically indicated for seizures related with Lennox-Gastaut syndrome (LGS) (Crumrine, 2011;Donegan, Dixon, Hemming, Tudur-Smith, & Marson, 2015;Hoy, 2016). Topic modeling showed a strong association of this agent with Lennox-Gastaut syndrome, a disorder which initiates seizures in children (Crumrine, 2011;Singh, 2016;Singh et al, 2016;VanStraten & Ng, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action of this drug is unknown, in vitro pharmacological studies suggest that lamotrigine inhibits voltage-sensitive sodium channels, thereby stabilizing neuronal membranes and consequently modulating presynaptic transmitter release of excitatory amino acids (e.g., glutamate and aspartate). Topic modeling revealed the association of this drug with the terms "dried blood spots", which suggests that research efforts have been focused on evaluating the safety profile of this drug, specifically in causing blood dyscrasias (Krasowski & McMillin, 2014;Milosheska, Grabnar, & Vovk, 2015;Baswan, Li, LaCount, & Kasting, 2016;Singh et al, 2016;.…”
Section: Discussionmentioning
confidence: 99%
“…The R packages "Cluster" (v 2.0.7.1) and "Dendextend' (1.8.0) was employed for this analysis. Significance testing for normal, non-normal and binary data was performed as described previously by the authors in other studies (Fleming et al, 2018;Hester et al, 2016;Karkare et al, 2014;Singh, 2015Singh, , 2016Singh et al, 2016;Singh, He, McNamara, & Danzer, 2013;Singh, Karkare, Baswan, & Singh, 2018;Singh, LaSarge, An, McAuliffe, & Danzer, 2015;Singh, Singh, Fatima, Kubo, & Singh, 2008;Singh & Karkare, 2017;Singh & Singh, 2017). De-identified data and the statistical analysis R code used was uploaded to an online repository.…”
Section: Discussionmentioning
confidence: 99%